«Diamonds and Mirages» - V. V. Vasilyev (Омский научный вестник: Серия "Общество. История. Современность")
Vadim Valeryevich Vasilyev is Doctor of Philosophy Sciences, Professor, Corresponding Member of Russian Academy of Sciences, and cofounder and member of the Academic Council of the Moscow Center for Consciousness Research at the Philosophy Department of the Lomonosov Moscow State University. The talk is dedicated to the specifics of analytic philosophy in Russia.